2018
DOI: 10.1155/2018/4627391
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Experimental Evidences of Hydrogen Sulfide Involvement in Lead-Induced Hypertension

Abstract: Lead- (Pb-) induced hypertension has been shown in humans and experimental animals and cardiovascular effects of hydrogen sulfide (H2S) have been reported previously. However, no studies examined involvement of H2S in Pb-induced hypertension. We found increases in diastolic blood pressure and mean blood pressure in Pb-intoxicated humans followed by diminished H2S plasmatic levels. In order to expand our findings, male Wistar rats were divided into four groups: Saline, Pb, NaHS, and Pb + NaHS. Pb-intoxicated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…The role of H 2 S in vascular diseases, inflammation, critical illness, reperfusion injury, various nervous system diseases, metabolic diseases and cancer was extensively reviewed [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Evidence in support of a role of H 2 S deficiency in vascular disorders, such as hypertension and atherosclerosis, is accumulating [ 79 , 80 ]. Other review articles addressed the vascular biology of H 2 S and the mechanisms of HHCy-induced vascular injury [ 81 , 82 ].…”
Section: H 2 S As a Gasotransmittermentioning
confidence: 99%
“…The role of H 2 S in vascular diseases, inflammation, critical illness, reperfusion injury, various nervous system diseases, metabolic diseases and cancer was extensively reviewed [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Evidence in support of a role of H 2 S deficiency in vascular disorders, such as hypertension and atherosclerosis, is accumulating [ 79 , 80 ]. Other review articles addressed the vascular biology of H 2 S and the mechanisms of HHCy-induced vascular injury [ 81 , 82 ].…”
Section: H 2 S As a Gasotransmittermentioning
confidence: 99%
“…Consequently, an increased Hcy/H 2 S ratio comes, for increase of the numerator and decrease of the denominator. In this condition vascular injuries especially happen, because vascular derangements [10,57] are added to the vascular injuries (due to H 2 S deficiency) [21,58]. Thus, the Hcy/H 2 S ratio can be considered as a biomarker able to induce vascular injuries more than HHcy and H 2 S deficiency esteemed separately.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have reported the relationship between H 2 S and hypertension related disorders ( 13 ). Additionally, decreased H 2 S plasmatic levels were also found in lead-induced HBP patients ( 14 ).…”
Section: Endogenous H 2 S In Hypertensionmentioning
confidence: 99%